(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Since the advent of independence in African countries, education generally focused on transforming these nations and redressing the ills of colonialism. Education in countries like Ghana, and Kenya, amongst others aimed at redressing the colonial legacy by creating a new world order marked by equality, mutual benefits and participation. However, this drive for equality, mutual benefits and participation has been beset by several challenges, ranging from access to funding. The recent and most devastating challenge has been the wave of violent student protests that have swept across African universities over the past decade. These protests led to the destruction of university structures and public property, as well as disruption of educational processes. While the reasons for these protests have been different in different countries, they all have become violent. This article argues that the culture of violence exhibited by students and their advocates is an inherited ideological trait that is gradually manifesting itself among students. In support of this argument, student protest is examined in the five regions of Africa; North, South, East, Central and West, spanning more than 20 different nations. The article concludes that because the culture of violence is an inherited one, the process will continue unless urgent steps are taken to ensure transformation and decolonisation. It also argues that universities need to create environments where students are comfortable to learn, thereby eradicating the need for protest.